BAURAN PEMASARAN DAN PERILAKU KONSUMEN DALAM PENGAMBILAN KEPUTUSAN PEMBELIAN CAPPUCCINO CINCAU - Sesunan, Terisia Muharam; Indriani, Yaktiworo; Listiana, Indah (Jurnal Ilmu-Ilmu Agribisnis, 2015)
This study aims to determine the relationship between marketing mix with purchase decision and consumer behavior on purchase decision, in addition to determine the influencing factors of the consumer characteristics on purchase decision making of cappuccino grass jelly . The research was conducted at the University of Lampung campus as a center of education in Bandar Lampung and in its area is most often found cappuccino tent grass jelly. This study used a survey method with qualitative and quantitative analysis. The population of this study was uncertain; therefore the samples of 100 students as consumers of cappuccino grass jelly and 10 traders as a manufacturer of cappuccino grass jelly were defined. The data was analyzed by the Spearman rank analysis and multiple linear regression analysis. The results showed that of the four marketing mix factors, only place, promotion and quality of service associated with the real decision-making process. Of the three elements of consumer behavior, only the personal element associated significantly with the process of consumer decision making of cappuccino grass jelly and of the seven predicted students’ characteristics as consumers of cappuccino grass jelly, only variable residence, gender, frequency of purchasing of instant coffee and frequency of grass jelly purchase had influences on purchase decisions of cappuccino grass jelly. Key words: consumer behavior, decision making, marketing mix